Analysis Of Social, Economic and Environmental Influences Motivation To Sell and Land Conversion : (Case Study in Ungasan Village, South Kuta Subdistrict, Badung Regency, Bali Province) - Angeline Jolie Taslim; Ni Made Tisnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Land conversion is the transformation of part or all of the land function from its original purpose to a different purpose. Land conversion is influenced by internal and external factors. These conditions can increase the motivation of landowners to sell their land. The purpose of this study is to directly influence location, environmental pressure, urgent needs, education level, selling price on motivation to sell and land conversion in Ungasan Village and to determine the indirect effect of location, environmental pressure, urgent needs, education level, selling price on land conversion in Ungasan Village through selling motivation. This research uses primary data using the Slovin formula with a total of 93 samples. The analysis technique used in this research is path analysis technique. Based on the results of the study, it shows that there is a direct influence of location, environmental pressure, urgent needs, education level, selling price on the motivation to sell and land conversion in Ungasan Village. Meanwhile, the variable level of education has no significant effect on land conversion in Ungasan Village.